2002
DOI: 10.2322/jjsass.50.477
|View full text |Cite
|
Sign up to set email alerts
|

Development of High-Performance Wind Turbine with Brimmed Diffuser

Abstract: We have developed a new wind turbine system that consists of a diffuser with a broad-ring brim at the exit periphery and a conventional wind turbine inside it. The new wind turbine has demonstrated power augmentation for a given turbine diameter and wind speed by a factor of about 2-3 compared with a bare wind turbine. This is because a very low-pressure region due to strong vortex formation behind the broad brim draws more mass flow to a turbine inside the diffuser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…The smoke-wire technique was employed for the flow visualization experiment. The experiments revealed that a diffuser-shaped structure can accelerate the wind at the entrance of the body, as shown in Figure 2 [8][9][10]. The reason is clarified through the flow visualization, as shown in Figure 3.…”
Section: Selection Of a Diffuser-type Structure As The Basic Formmentioning
confidence: 87%
See 1 more Smart Citation
“…The smoke-wire technique was employed for the flow visualization experiment. The experiments revealed that a diffuser-shaped structure can accelerate the wind at the entrance of the body, as shown in Figure 2 [8][9][10]. The reason is clarified through the flow visualization, as shown in Figure 3.…”
Section: Selection Of a Diffuser-type Structure As The Basic Formmentioning
confidence: 87%
“…The inlet shroud makes wind easy to flow into the diffuser. Viewed as a whole, the collection-acceleration device consists of a venturi-shaped structure with a brim [8][9][10]. As for other parameters, we have examined the diffuser opening angle, the hub ratio, and the center-body length [10][11][12].…”
Section: Idea Of a Ring-type Plate Which Forms Vortices (It Is Calledmentioning
confidence: 99%
“…It can be seen that the static pressure increases near the inlet of type A and hinders the flow from entering the collection device. On the other hand, the static pressure near the inlet of type B decreases and the flow is easily drawn into the collection device [8]. However, in type B, backflow is created inside the collection device.…”
Section: Performance Characteristics For the Collection Device Onmentioning
confidence: 99%
“…Open and shallow water channels are constrained in the height direction. Accordingly, the type described here 2 International Journal of Rotating Machinery differs from conventional wind turbines [7][8][9][10][11] and hydraulic turbines [12][13][14][15] in which the diffuser section of the collection device is constant vertically and varies horizontally. Thus, the outer diameter of the runner is almost as large as the water depth.…”
Section: Introductionmentioning
confidence: 99%
“…Open channels with shallow water depth are constrained in the height direction. Accordingly, the hydraulic turbine described here differs from conventional wind turbines [8,[12][13][14] and hydraulic turbines [15][16][17][18] in which the diffuser section of the collection device is constant vertically and varies horizontally. The brim was attached to the left and right sides of the outlet of the collection device.…”
Section: Hydraulic Turbine Test Piecementioning
confidence: 99%